Striatum Shape Hypertrophy in Early Stage Parkinson’s Disease With Excessive Daytime Sleepiness - Gong, Liang; Li, Huaisu; Yang, Dan; Peng, Yinwei; Liu, Duan; Zhong, Ming; Zhang, Bei; Xu, Ronghua; Kang, Jian (Frontiers in Neuroscience, 2020)
Introduction: Excessive daytime sleepiness (EDS) is one of the common and burdensome non-motor symptoms of Parkinson's disease (PD). However, the underlying neuropathology mechanism in PD patients with EDS remains unclear. The present study aims to delineate potential locations of structural alteration of subcortical regions in early-stage and drug naïve PD patients with EDS. Methods: The study had 252 patients with PD and 92 matched healthy controls (HC). EDS was estimated with the Epworth sleepiness scale, with a cutoff of 10. Ultimately, 59 patients were considered as PD patients with EDS (PD-EDS). The remaining 193 were PD patients without EDS (PD-nEDS). FMRIB's Integrated Registration and Segmentation Tool (FIRST) was employed to assess the volumetric and surface alterations of subcortical nuclei in PD and PD-EDS. Results: Volumetric analyses found no difference in the subcortical nucleus volume between PD and HC, or PD-EDS and PD-nEDS groups. The shape analyses revealed that the local atrophic changes in bilateral caudate and right putamen in patients with PD. In addition, the hypertrophic changes were located in the right putamen and left pallidum in PD-EDS than in PD-nEDS. Conclusion Our findings revealed the regional hypertrophy of the striatum in PD patients with EDS. Our results indicate that local hypertrophic striatum would be a valuable early biomarker for detecting the alteration in PD patients with EDS. The shape analysis contributes valuable information when investigating PD patients with EDS.